Evaluating a structured expert elicitation approach for adaptive conservation management based on lessons from five years in practice - Helen J. Mayfield; James Brazill‐Boast; Mick Andren; Michiala Bowen; Adam Fawcett; Trent Forge; Luke Foster; Ross Goldingay; Paul Hillier; Meagan Hinds; Simon Lee; Erica Mahon; et al. (Conservation Biology, 2026)
Adaptive management of threatened species relies on having ex ante estimates of species’ responses to different interventions. Structured expert elicitation is often used to generate these estimates, but comparisons of these expert‐predicted outcomes with observed results are rare. This study aims to evaluate the utility of expert elicitation for adaptive management in the New South Wales Saving our Species program in Australia by revisiting six species management plans that were generated from tailored structured elicitation guidelines developed five years prior. Each species’ management plan included a defined scope, conceptual model, monitoring indicators, and estimated response to management curves under different scenarios. Experts reviewed the conceptual models after five years of management and compared the predicted response to management with observed monitoring data. In three of the six case studies, observed outcomes closely matched predictions. Where predictions diverged, factors such as unanticipated new threats and unexpected responses to interventions potentially contributed to discrepancies. However, in all cases, the structured approach provided a clear logic for planning, enabling managers to systematically refine their understanding. The conceptual models and response curves were valuable for collaborating, communicating, and generating hypotheses for unexpected results. This work demonstrates the value of tailored guidelines in supporting adaptive management processes and showcases the value of documenting expert knowledge in management settings with high uncertainty.

Factors influencing public willingness to participate in population-based hereditary cancer genetic testing: a qualitative study of public preferences - Diego R. Sanchez-Vazquez; Jonathan Avery; Whitney Qualls; Colene Bentley; Helen McTaggart-Cowan; Julianne McLeod; Lesa Dawson; Stuart Peacock (Familial Cancer, 2026)

A horizon scan of biological conservation issues for 2026 - William J. Sutherland; Stuart H.M. Butchart; Stewart J. Clarke; Nigel R. Doar; Helen Doran; Imogen C. Douglas; Daniel J. Field; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Hermanni Kaartokallio; et al. (Trends in Ecology & Evolution, 2026)

Biophysical drivers of coral reef community structure across a tropical benthic seascape - Rosalie A. Wright; Sasha Hills; Courtney E. Stuart; Kaya Malhi; Pirta Palola; Cassandra E. Benkwitt; Hannah E. Epstein; Teva Beguet; Helen V. Ford; Melissa Ward; Lisa M. Wedding (Coral Reefs, 2025)
Coral reefs are global biodiversity hotspots, important for ocean health and providing ecosystem services for thousands of species (including humans). Coral benthic communities form the structural basis of these ecosystems, influencing ecological processes and ecosystem functions. For thousands of years, coral benthic communities have been driven by naturally occurring properties of the environment, which we refer to as biophysical drivers. However, as humans increasingly encroach on and alter coastal marine ecosystems, anthropogenic conditions may override biophysical drivers, making it challenging to identify the sources of changes in community composition and consequent ecosystem functioning. Here, we use multivariate analyses to demonstrate that bathymetric slope (surface steepness) and intercardinal bearing, a proxy for wind and wave exposure, are significant drivers of benthic composition across Tetiaroa, French Polynesia, a remote coral atoll where the influences of biophysical conditions have not been previously investigated. Distance-based redundancy analysis concluded that together, these biophysical variables explained 66.02% of the variance in benthic community composition. Determining the most important drivers of benthic community composition in this area of minimal human influence provides baseline data for natural coral reef ecosystems. This information will help us understand and predict coral reef community responses to changing environmental conditions and guide conservation and restoration efforts of this ecologically important atoll.

International Consortium on Ageing-Related Pathologies (ICCARP) Audiovestibular Group: fostering international consensus to refine International Classification of Diseases (ICD-11) codes for hearing loss across the life course - Dialechti Tsimpida; Michael A. Akeroyd; Barry L. Bentley; Shuvarthi Bhattacharjee; Michael R. Bowl; Emma Broome; Stuart R. G. Calimport; Sian Calvert; Gary Christopher; Tom Dening; Silvia Di Bonaventura; Ankita Goswami; et al. (GeroScience, 2025)

Latitudinal gradients in herbivorous and detritivorous reef fish productivity - Sterling B. Tebbett; Helen F. Yan; Scott Bennett; Graham J. Edgar; Scott D. Ling; Rick D. Stuart-Smith; David R. Bellwood (Reviews in Fish Biology and Fisheries, 2025)

Evaluating the effectiveness of seabird bycatch mitigation measures for pelagic longlines in the South Atlantic - James B. Bell; Johannes H. Fischer; Ana P.B. Carneiro; Shane Griffiths; Alessandra Bielli; Sebastián Jiménez; Steffen Oppel; Richard A. Phillips; Helen M. Wade; Oliver Yates; Stuart A. Reeves (Biological Conservation, 2025)

Riverine concentrations and export of dissolved silicon, and potential controls on nutrient stoichiometry, across the land–ocean continuum in Great Britain - Andrew M. Tye; Helen P. Jarvie; Bryan M. Spears; Nancy B. Dise; Jennifer L. Williamson; Dan J. Lapworth; Don Monteith; Richard Sanders; Daniel J. Mayor; Michael J. Bowes; Michael Bowes; Annette Burden; et al. (Journal of Hydrology, 2024)

Association between ambient temperature and common allergenic pollen and fungal spores: A 52-year analysis in central England, United Kingdom - Holly C.Y. Lam; Samuel Anees-Hill; Jack Satchwell; Fiona Symon; Helen Macintyre; Catherine H. Pashley; Emma L. Marczylo; Philippa Douglas; Stuart Aldridge; Anna Hansell (Science of The Total Environment, 2024)

Continuous home cage monitoring of activity and sleep in mice during repeated paroxetine treatment and discontinuation - Helen M. Collins; Raquel Pinacho; S. K. Eric Tam; Trevor Sharp; David M. Bannerman; Stuart N. Peirson (Psychopharmacology, 2023)
Rationale Non-invasive home cage monitoring is emerging as a valuable tool to assess the effects of experimental interventions on mouse behaviour. A field in which these techniques may prove useful is the study of repeated selective serotonin reuptake inhibitor (SSRI) treatment and discontinuation. SSRI discontinuation syndrome is an under-researched condition that includes the emergence of sleep disturbances following treatment cessation. Objectives We used passive infrared (PIR) monitoring to investigate changes in activity, sleep, and circadian rhythms during repeated treatment with the SSRI paroxetine and its discontinuation in mice. Methods Male mice received paroxetine (10 mg/kg/day, s.c. ) for 12 days, then were swapped to saline injections for a 13 day discontinuation period and compared to mice that received saline injections throughout. Mice were continuously tracked using the Continuous Open Mouse Phenotyping of Activity and Sleep Status (COMPASS) system. Results Repeated paroxetine treatment reduced activity and increased behaviourally-defined sleep in the dark phase. These effects recovered to saline-control levels within 24 h of paroxetine cessation, yet there was also evidence of a lengthening of sleep bouts in the dark phase for up to a week following discontinuation. Conclusions This study provides the first example of how continuous non-invasive home cage monitoring can be used to detect objective behavioural changes in activity and sleep during and after drug treatment in mice. These data suggest that effects of paroxetine administration reversed soon after its discontinuation but identified an emergent change in sleep bout duration, which could be used as a biomarker in future preclinical studies to prevent or minimise SSRI discontinuation symptoms.

Negative effects of urbanisation on diurnal and nocturnal pollen‐transport networks - Emilie E. Ellis; Jill L. Edmondson; Kathryn H. Maher; Helen Hipperson; Stuart A. Campbell (Ecology Letters, 2023)
Pollinating insects are declining due to habitat loss and climate change, and cities with limited habitat and floral resources may be particularly vulnerable. The effects of urban landscapes on pollination networks remain poorly understood, and comparative studies of taxa with divergent niches are lacking. Here, for the first time, we simultaneously compare nocturnal moth and diurnal bee pollen‐transport networks using DNA metabarcoding and ask how pollination networks are affected by increasing urbanisation. Bees and moths exhibited substantial divergence in the communities of plants they interact with. Increasing urbanisation had comparable negative effects on pollen‐transport networks of both taxa, with significant declines in pollen species richness. We show that moths are an important, but overlooked, component of urban pollen‐transport networks for wild flowering plants, horticultural crops, and trees. Our findings highlight the need to include both bee and non‐bee taxa when assessing the status of critical plant‐insect interactions in urbanised landscapes.

Wastewater-based monitoring reveals geospatial-temporal trends for antibiotic-resistant pathogens in a large urban community - Zillur Rahman; Weijia Liu; Lara Stapleton; Nikki Kenters; Dewa A.P. Rasmika Dewi; Ori Gudes; Helen Ziochos; Stuart J. Khan; Kaye Power; Mary-Louise McLaws; Torsten Thomas (Environmental Pollution, 2023)

De novo mutations in the BMP signaling pathway in lambdoid craniosynostosis - Andrew T. Timberlake; Emre Kiziltug; Sheng Chih Jin; Carol Nelson-Williams; Erin Loring; August Allocco; Arnaud Marlier; Siddharth Banka; Helen Stuart; Maria Rita Passos-Buenos; Rafael Rosa; Silvia R. Rogatto; et al. (Human Genetics, 2023)

Funding evidence‐based conservation - Danni Parks; Nida Al‐Fulaij; Clare Brook; Stuart H. M. Butchart; Jean‐Gaël Collomb; David Cope; Simon Dowell; Becky Falkingham; Winifred F. Frick; Douglas Gibbs; Emily E. Gray; Nicolas Heard; et al. (Conservation Biology, 2022)

Neurostructural and Neurophysiological Correlates of Multiple Sclerosis Physical Fatigue: Systematic Review and Meta-Analysis of Cross-Sectional Studies - Paula M. Ellison; Stuart Goodall; Niamh Kennedy; Helen Dawes; Allan Clark; Valerie Pomeroy; Martin Duddy; Mark R. Baker; John M. Saxton (Neuropsychology Review, 2022)
Fatigue is one of the most debilitating symptoms for people with multiple sclerosis (PwMS). By consolidating a diverse and conflicting evidence-base, this systematic review and meta-analysis aimed to gain new insights into the neurobiology of MS fatigue. MEDLINE, ProQuest, CINAHL, Web of Science databases and grey literature were searched using Medical Subject Headings. Eligible studies compared neuroimaging and neurophysiological data between people experiencing high (MS-HF) versus low (MS-LF) levels of perceived MS fatigue, as defined by validated fatigue questionnaire cut-points. Data were available from 66 studies, with 46 used for meta-analyses. Neuroimaging studies revealed lower volumetric measures in MS-HF versus MS-LF for whole brain (22.74 ml; 95% CI: -37.72 to -7.76 ml; p = 0.003), grey matter (18.81 ml; 95% CI: 29.60 to 8.03 ml; p < 0.001), putamen (0.40 ml; 95% CI: 0.69 to 0.10 ml; p = 0.008) and acumbens (0.09 ml; 95% CI: 0.15 to 0.03 ml; p = 0.003) and a higher volume of T1-weighted hypointense lesions (1.10 ml; 95% CI: 0.47 to 1.73 ml; p < 0.001). Neurophysiological data showed reduced lower-limb maximum voluntary force production (19.23 N; 95% CI: 35.93 to 2.53 N; p = 0.02) and an attenuation of upper-limb (5.77%; 95% CI:8.61 to 2.93%; p < 0.0001) and lower-limb (2.16%; 95% CI:4.24 to 0.07%; p = 0.04) skeletal muscle voluntary activation, accompanied by more pronounced upper-limb fatigability (5.61%; 95% CI: -9.57 to -1.65%; p = 0.006) in MS-HF versus MS-LF. Results suggest that MS fatigue is characterised by greater cortico-subcortical grey matter atrophy and neural lesions, accompanied by neurophysiological decrements, which include reduced strength and voluntary activation. Prospero registration Prospero registration number: CRD42016017934

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Workflow for the Generation of Expert-Derived Training and Validation Data: A View to Global Scale Habitat Mapping - Chris M. Roelfsema; Mitchell Lyons; Nicholas Murray; Eva M. Kovacs; Emma Kennedy; Kathryn Markey; Rodney Borrego-Acevedo; Alexandra Ordoñez Alvarez; Chantel Say; Paul Tudman; Meredith Roe; Jeremy Wolff; et al. (Frontiers in Marine Science, 2021)
Our ability to completely and repeatedly map natural environments at a global scale have increased significantly over the past decade. These advances are from delivery of a range of on-line global satellite image archives and global-scale processing capabilities, along with improved spatial and temporal resolution satellite imagery. The ability to accurately train and validate these global scale-mapping programs from what we will call “reference data sets” is challenging due to a lack of coordinated financial and personnel resourcing, and standardized methods to collate reference datasets at global spatial extents. Here, we present an expert-driven approach for generating training and validation data on a global scale, with the view to mapping the world’s coral reefs. Global reefs were first stratified into approximate biogeographic regions, then per region reference data sets were compiled that include existing point data or maps at various levels of accuracy. These reference data sets were compiled from new field surveys, literature review of published surveys, and from individually sourced contributions from the coral reef monitoring and management agencies. Reference data were overlaid on high spatial resolution satellite image mosaics (3.7 m × 3.7 m pixels; Planet Dove) for each region. Additionally, thirty to forty satellite image tiles; 20 km × 20 km) were selected for which reference data and/or expert knowledge was available and which covered a representative range of habitats. The satellite image tiles were segmented into interpretable groups of pixels which were manually labeled with a mapping category via expert interpretation. The labeled segments were used to generate points to train the mapping models, and to validate or assess accuracy. The workflow for desktop reference data creation that we present expands and up-scales traditional approaches of expert-driven interpretation for both manual habitat mapping and map training/validation. We apply the reference data creation methods in the context of global coral reef mapping, though our approach is broadly applicable to any environment. Transparent processes for training and validation are critical for usability as big data provide more opportunities for managers and scientists to use global mapping products for science and conservation of vulnerable and rapidly changing ecosystems.

Using structured eradication feasibility assessment to prioritize the management of new and emerging invasive alien species in Europe - Olaf Booy; Pete A. Robertson; Niall Moore; Jess Ward; Helen E. Roy; Tim Adriaens; Richard Shaw; Johan Van Valkenburg; Gabrielle Wyn; Sandro Bertolino; Olivier Blight; Etienne Branquart; et al. (Global Change Biology, 2020)
Prioritizing the management of invasive alien species (IAS) is of global importance and within Europe integral to the EU IAS regulation. To prioritize management effectively, the risks posed by IAS need to be assessed, but so too does the feasibility of their management. While the risk of IAS to the EU has been assessed, the feasibility of management has not. We assessed the feasibility of eradicating 60 new (not yet established) and 35 emerging (established with limited distribution) species that pose a threat to the EU, as identified by horizon scanning. The assessment was carried out by 34 experts in invasion management from across Europe, applying the Non‐Native Risk Management scheme to defined invasion scenarios and eradication strategies for each species, assessing the feasibility of eradication using seven key risk management criteria. Management priorities were identified by combining scores for risk (derived from horizon scanning) and feasibility of eradication. The results show eradication feasibility score and risk score were not correlated, indicating that risk management criteria evaluate different information than risk assessment. In all, 17 new species were identified as particularly high priorities for eradication should they establish in the future, whereas 14 emerging species were identified as priorities for eradication now. A number of species considered highest priority for eradication were terrestrial vertebrates, a group that has been the focus of a number of eradication attempts in Europe. However, eradication priorities also included a diverse range of other taxa (plants, invertebrates and fish) suggesting there is scope to broaden the taxonomic range of attempted eradication in Europe. We demonstrate that broad scale structured assessments of management feasibility can help prioritize IAS for management. Such frameworks are needed to support evidence‐based decision‐making.

How can wages sustain a living? By getting ahead of the curve - Stuart Colin Carr; Molefe Maleka; Ines Meyer; Marie-Louise Barry; Jarrod Haar; Jane Parker; James Arrowsmith; Christian Yao; Darrin Hodgetts; Harvey Jones; Amanda Young-Hausner; Emeline Afeaki-Mafile’o; et al. (Sustainability Science, 2018)

Ex-post assessment of genetically modified, low level presence in Canadian flax - Helen M. Booker; Eric G. Lamb; Stuart J. Smyth (Transgenic Research, 2017)

Mapping species distributions: A comparison of skilled naturalist and lay citizen science recording - René van der Wal; Helen Anderson; Annie Robinson; Nirwan Sharma; Chris Mellish; Stuart Roberts; Ben Darvill; Advaith Siddharthan (Ambio, 2015)

An assessment of endocrine activity in Australian rivers using chemical and in vitro analyses - Philip D. Scott; Michael Bartkow; Stephen J. Blockwell; Heather M. Coleman; Stuart J. Khan; Richard Lim; James A. McDonald; Helen Nice; Dayanthi Nugegoda; Vincent Pettigrove; Louis A. Tremblay; Michael St. J. Warne; et al. (Environmental Science and Pollution Research, 2014)

The origin of Ag–Au–S–Se minerals in adularia-sericite epithermal deposits: constraints from the Broken Hills deposit, Hauraki Goldfield, New Zealand - Helen A. Cocker; Jeffrey L. Mauk; Stuart D. C. Rabone (Mineralium Deposita, 2013)

Multi-parameter flow cytometry and cell sorting reveal extensive physiological heterogeneity in Bacillus cereus batch cultures - Andrew Want; Helen Hancocks; Colin R. Thomas; Stuart M. Stocks; Gerhard Nebe-von-Caron; Christopher J. Hewitt (Biotechnology Letters, 2011)

Detection of microbial biomass by intact polar membrane lipid analysis in the water column and surface sediments of the Black Sea - Florence Schubotz; Stuart G. Wakeham; Julius S. Lipp; Helen F. Fredricks; Kai‐Uwe Hinrichs (Environmental Microbiology, 2009)
Summary The stratified water column of the Black Sea produces a vertical succession of redox zones, stimulating microbial activity at the interfaces. Our study of intact polar membrane lipids (IPLs) in suspended particulate matter and sediments highlights their potential as biomarkers for assessing the taxonomic composition of live microbial biomass. Intact polar membrane lipids in oxic waters above the chemocline represent contributions of bacterial and eukaryotic photosynthetic algae, while anoxygenic phototrophic bacteria and sulfate‐reducing bacteria comprise a substantial amount of microbial biomass in deeper suboxic and anoxic layers. Intact polar membrane lipids such as betaine lipids and glycosidic ceramides suggest unspecified anaerobic bacteria in the anoxic zone. Distributions of polar head groups and core lipids show planktonic archaea below the oxic zone; methanotrophic archaea are only a minor fraction of archaeal biomass in the anoxic zone, contrasting previous observations based on the apolar derivatives of archaeal lipids. Sediments contain algal and bacterial IPLs from the water column, but transport to the sediment is selective; bacterial and archaeal IPLs are also produced within the sediments. Intact polar membrane lipid distributions in the Black Sea are stratified in accordance with geochemical profiles and provide information on vertical successions of major microbial groups contributing to suspended biomass. This study vastly extends our knowledge of the distribution of complex microbial lipids in the ocean.

Order parameter coupling in leucite: a calorimetric study - Helen Newton; Stuart A. Hayward; Simon A. T. Redfern (Physics and Chemistry of Minerals, 2008)

Global negative vegetation feedback to climate warming responses of leaf litter decomposition rates in cold biomes - Johannes H.C. Cornelissen; Peter M. Van Bodegom; Rien Aerts; Terry V. Callaghan; Richard S.P. Van Logtestijn; Juha Alatalo; F. Stuart Chapin; Renato Gerdol; Jon Gudmundsson; Dylan Gwynn‐Jones; Anne E. Hartley; David S. Hik; et al. (Ecology Letters, 2007)
Whether climate change will turn cold biomes from large long‐term carbon sinks into sources is hotly debated because of the great potential for ecosystem‐mediated feedbacks to global climate. Critical are the direction, magnitude and generality of climate responses of plant litter decomposition. Here, we present the first quantitative analysis of the major climate‐change‐related drivers of litter decomposition rates in cold northern biomes worldwide. Leaf litters collected from the predominant species in 33 global change manipulation experiments in circum‐arctic‐alpine ecosystems were incubated simultaneously in two contrasting arctic life zones. We demonstrate that longer‐term, large‐scale changes to leaf litter decomposition will be driven primarily by both direct warming effects and concomitant shifts in plant growth form composition, with a much smaller role for changes in litter quality within species. Specifically, the ongoing warming‐induced expansion of shrubs with recalcitrant leaf litter across cold biomes would constitute a negative feedback to global warming. Depending on the strength of other (previously reported) positive feedbacks of shrub expansion on soil carbon turnover, this may partly counteract direct warming enhancement of litter decomposition.

Sequencing EVC and EVC2 identifies mutations in two-thirds of Ellis–van Creveld syndrome patients - Stuart W. J. Tompson; Victor L. Ruiz-Perez; Helen J. Blair; Stephanie Barton; Victoria Navarro; Joanne L. Robson; Michael J. Wright; Judith A. Goodship (Human Genetics, 2006)

Modulation of corneal endothelial hydration control mechanisms by Rolipram - Christopher G. Wigham; Helen C. Turner; Jeremy Swan; Stuart A. Hodson (Pflügers Archiv - European Journal of Physiology, 2000)